Metastatic non‐small cell lung cancer: a benchmark for quality end‐of‐life cancer care?. Issue 3 (16th February 2015) - Philip, Jennifer; Hudson, Peter; Bostanci, Adam; Street, Annette; Horey, Dell E; Aranda, Sanchia; Zordan, Rachel; Rumbold, Bruce D; Moore, Gaye; Sundararajan, Vijaya
Abstract: Objectives: To investigate the quality of end‐of‐life care for patients with metastatic non‐small cell lung cancer (NSCLC). Design and participants: Retrospective cohort study of patients from first hospitalisation for metastatic disease until death, using hospital, emergency department and death registration data from Victoria, Australia, between 1 July 2003 and 30 June 2010. Main outcome measures: Emergency department and hospital use; aggressiveness of care including intensive care and chemotherapy in last 30 days; palliative and supportive care provision; and place of death. Results: Metastatic NSCLC patients underwent limited aggressive treatment such as intensive care (5%) and chemotherapy (< 1%) at the end of life; however, high numbers died in acute hospitals (42%) and 61% had a length of stay of greater than 14 days in the last month of life. Although 62% were referred to palliative care services, this occurred late in the illness. In a logistic regression model adjusted for year of metastasis, age, sex, metastatic site and survival, the odds ratio (OR) of dying in an acute hospital bed compared with death at home or in a hospice unit decreased with receipt of palliative care (OR, 0.25; 95% CI, 0.21–0.30) and multimodality supportive care (OR, 0.65; 95% CI, 0.56–0.75). Conclusion: Because early palliative care for patients with metastatic NSCLC is recommended, we propose that this group be considered a benchmark of quality end‐of‐life care. Future work is required to determine appropriate quality‐of‐care targets in this and other cancer patient cohorts, with particular focus on the timeliness of palliative care engagement.